APPLYING SCANNING AND SKIMMING SKILLS TO UNDERSTAND LIFE SKILLS READING - slamet basuki (STIBA IEC JAKARTA, 2018)
The purpose of life skills reading is to extract information that will assist the reader in performing some task of work or for daily life. Most formal school students who are given training on the life skills reading, they can comprehend the meaning of the text. Since the purpose of life of reading skills is to derive meaning from it, the readers should not translate word by word what they have read. Therefore skimming and scanning skills are important to be trained to senior school students as well as college students. This research is given to the senior school students. The findings show that students who have skimming and scanning skills are able to comprehend the meaning of the texts. By obtaining skills on reading such those kinds of text, students are expected to be able to comprehend what they have read and assist people who need help in understanding the life skills reading. This research suggests the teachers to encourage students to be able to know the meaning of the life skills reading so that the people around them can take the benefit of him/her. It also has the implication that teachers can give their students skimming and scanning skills in the reading activities